HepatoNet1: a comprehensive metabolic reconstruction of the human hepatocyte for the analysis of liver physiology - Gille, Christoph; Bölling, Christian; Hoppe, Andreas; Bulik, Sascha; Hoffmann, Sabrina; Hübner, Katrin; Karlstädt, Anja; Ganeshan, Ramanan; König, Matthias; Rother, Kristian; Weidlich, Michael; Behre, Jörn Arnold; et al. (Molecular systems biology)
We present HepatoNet1, the first reconstruction of a comprehensive metabolic network of the human hepatocyte that is shown to accomplish a large canon of known metabolic liver functions. The network comprises 777 metabolites in six intracellular and two extracellular compartments and 2539 reactions, including 1466 transport reactions. It is based on the manual evaluation of >1500 original scientific research publications to warrant a high-quality evidence-based model. The final network is the result of an iterative process of data compilation and rigorous computational testing of network functionality by means of constraint-based modeling techniques. Taking the hepatic detoxification of ammonia as an example, we show how the availability of nutrients and oxygen may modulate the interplay of various metabolic pathways to allow an efficient response of the liver to perturbations of the homeostasis of blood compounds.
Gesehen am 23.03.2023